The potentials of Robusta (Coffea Robusta L.) and Arabica (Coffea Arabica L.) coffee leaf by-product as anti-diabetic drinks - Kiki Fibrianto; Azarul ‘Izza; Erryana Martati; Igoy Arya Bimo (Hasanuddin University Food Science and Technology Study Program, 2023)
1) Background: It has been known that coffee leaf contain various bioactives and antioxidants. While diabetes can be indicated by the damage of pancreatic beta cells, numerous studies have reported that many kinds of antioxidants can recover the beta cells. As a result, coffee leaf tea has the potential to be developed as an anti-diabetic beverage. The current study used in vivo experiments to investigate the functionality of coffee leaf tea for diabetic therapy; 2) Methods: Robusta and Arabica coffee leaf were processed as oolong tea. All samples were soft-infused. Healthy and diabetic rats (induced with STZ intraperitonially at 80 mg/kg BW) were treated by injecting the softly infused coffee leaf tea 12 ml/kg BW/day for 28 days; 3) Results: Compared to the glibenclamide treatment, diabetic rats injected with Robusta coffee leaf tea were better at lowering blood sugar (p-value <0.05), as well as maintaning body weight. This is supported by the fact that the number of pancreatic beta cells in diabetic rats injected with Robusta coffee leaf tea was significantly higher than in glibenclamide treated rats (pvalue <0.05). Coffee leaf tea tend to have a lighter sensory profile than oolong tea; 4) Conclusions: It can be concluded that Robusta coffee leaf tea tends to be potentially developed as anti-diabetic drink since it can recover damaged pancreatic beta cells better than glibenclamide, thus helping to decrease blood sugar.